2019
DOI: 10.22460/eltin.v7i1.p12-22
|View full text |Cite
|
Sign up to set email alerts
|

Efl Students’ Perception Towards the Use of Bahasa Indonesia in an English Classroom

Abstract: The issue of using first language (L1) in teaching English has always been a controversy in the field of teaching and learning English.  The purpose of this study was to investigate the English as Foreign Language (EFL) students’ perceptions towards the use of L1 (Bahasa Indonesia) in the English classroom. In this study, the descriptive qualitative method was employed.  The participants involved in this study are 40 EFL students in the second semester who learn General English in IKIP Siliwangi. A questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Moreover, Sa'd and Qadermazi (2015) argue that the mother tongue use should be limited, judicious, and occasional for a better approach in the EFL classroom to facilitate the English learning process, for instance, to clarify the explanation of linguistic points (lexical, grammatical, etc.). Then, Resmini (2019) also found that the use of mother tongue in EFL classrooms brought negative perceptions to the students. They gave negative views, but the students also recognized the advantages of limited mother tongue use in certain situations.…”
Section: Students' Perceptions Toward the Use Of The Mother Tongue In Eflmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Sa'd and Qadermazi (2015) argue that the mother tongue use should be limited, judicious, and occasional for a better approach in the EFL classroom to facilitate the English learning process, for instance, to clarify the explanation of linguistic points (lexical, grammatical, etc.). Then, Resmini (2019) also found that the use of mother tongue in EFL classrooms brought negative perceptions to the students. They gave negative views, but the students also recognized the advantages of limited mother tongue use in certain situations.…”
Section: Students' Perceptions Toward the Use Of The Mother Tongue In Eflmentioning
confidence: 99%
“…Therefore, it will be beneficial to understand others' points of view or perspectives toward the things of their surroundings. Also, it could be the way we judge or evaluate others and things that led people to perceive the thing that is defined as individuals' attitudes and character (Resmini, 2019).…”
Section: Previous Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Student perceptions have been frequently identified with two objectives in the literature: perceptions of themselves, and perceptions of the learning condition (Wesely, 2012). How students understand and make sense of themselves and their own learning is perceived as perceptions of themselves (Waddington, 2019;Resmini, 2019). Learner perceptions of the learning condition are comprised of how students undergo and comprehend aspects of the classroom, like teacher behaviors (Demiroz & Yeşilyurt, 2015).…”
Section: Communicative Language Teaching (Clt)mentioning
confidence: 99%
“…However, studies investigate the use of Bahasa Indonesia in English classes, particularly in senior high school level, are still limited. Related previous studies (Julianti, Atmowardoyo & Mahmud, 2016;Resmini, 2019;Usadiati, 2009;Zacharias, 2003) were conducted in tertiary education level. Only a few studies (Anggrahini, 2019;Hasrina, Aziz & Fitriani, 2018;and Pardede, 2018) focused on senior high school students.…”
Section: Introductionmentioning
confidence: 95%